Efficacy and Safety of Trazodone and Gabapentin Fixed-Dose Combination in Patients Affected by Painful Diabetic Neuropathy: Randomized, Controlled, Dose-Finding Study - Solomon Tesfaye; Ponnusamy Saravanan; Edvard Ehler; Karel Zinek; Ilona Palka-Kisielowska; Marcin Nastaj; Pierre Serusclat; Paola Lipone; Andrea Vergallo; Elisa Quarchioni; Fabrizio Calisti; Alessandro Comandini; et al. (Pain and Therapy, 2024)
Abstract Introduction Up to 50% of diabetic patients with neuropathy suffer from chronic pain, namely painful diabetic neuropathy (PDN), an unmet medical need with significant impact on quality of life. Gabapentin is widely used for PDN, albeit with frequent dose-limiting effects. Trazodone, an antidepressant with multi-modal action, has shown promising results when given at low doses as an add-on to gabapentin. Upon previous clinical trials and experimental evidence, a fixed-dose combination (FDC) of both compounds, at low doses, was developed for neuropathic pain. Methods This was a phase II, randomized, double-blind, placebo and reference controlled, dose-finding, multicenter, international, prospective study. Male and female diabetic patients aged 18–75 years and affected by PDN were eligible for enrolment. Patients were randomized (1:1:1:1:2 ratio) to trazodone and gabapentin (Trazo/Gaba) 2.5/25 mg t.i.d. for 8 weeks, Trazo/Gaba 5/50 mg t.i.d. for 8 weeks, Trazo/Gaba 10/100 mg t.i.d. for 8 weeks, gabapentin (Gaba), or placebo (PLB). The aim of the study was to collect preliminary information on the effect of the 3 different FDCs of Trazo/Gaba on pain intensity based on the 11-point numeric rating score (NRS) after 8 weeks of treatment. The secondary objectives were the evaluation of the percentage of responders, neuropathic pain symptoms, anxiety, sleep, quality of life, safety, and tolerability. The primary efficacy endpoint was evaluated with last observation carried out forward (LOCF), using an analysis of covariance (ANCOVA), including treatment and centers as factors and baseline as covariate and applying linear contrast test, excluding the active treatment. Only if the linear contrast test was significant (p < 0.05), the step-down Dunnett test would be used to determine the minimum effective dose significantly different from PLB. If linearity was not verified, an adjusted ANCOVA model and comparisons with Dunnett test were performed. Before the application of the ANCOVA model, the non-significance of interaction treatment per baseline was verified. Results A total of 240 patients were included in the modified intention-to-treat (m-ITT) population: 39 in Trazo/Gaba 2.5/25 mg, 38 in Trazo/Gaba 5/50 mg, 37 in Trazo/Gaba 10/100 mg, 83 in PLB, and 43 in Gaba. After 8 weeks of treatment, changes of the average daily pain score based on the 11-point NRS from baseline were − 2.52 ± 2.31 in Trazo/Gaba 2.5/25 mg group, − 2.24 ± 1.96 in Trazo/Gaba 5/50 mg group, − 2.46 ± 2.12 in Trazo/Gaba 10/100 mg group, − 1.92 ± 2.21 in Gaba group, and − 2.02 ± 1.95 in the PLB group. The linear contrast test did not result in significant differences (p > 0.05) among treatment groups. Consequently, the minimum effective dose against PLB was not determined. The multiple comparison with Dunnett adjustment did not show any statistically significant differences vs. PLB after 8 weeks of treatment: Trazo/Gaba 2.5/25 mg (95% confidence interval (CI) − 1.2739, 0.2026; p = 0.1539); Trazo/Gaba 5/50 mg (95% CI − 0.9401, 0.5390; p = 0.5931); Trazo/Gaba 10/100 mg (95% CI − 1.0342, 0.4582; p = 0.4471). However, patients receiving the lowest dose of Trazo/Gaba 2.5/25 mg showed a statistically significant difference to PLB after 6 weeks of treatment (95% CI − 1.6648, − 0.2126; p = 0.0116). Positive results were also found for responder patients, other items related to the pain, anxiety, depression, sleep, and quality of life, consistently in favor to the lowest Trazo/Gaba FDC. Two serious adverse events (SAEs) occurred but were judged unrelated to the study treatment. Treatment-emergent adverse events (TEAEs) were mainly mild-to-moderate in intensity and involved primarily nervous system, gastrointestinal disorders, and investigations. Conclusions The primary end point of the study was the change from baseline of the average daily pain score based on the 11-point NRS after 8 weeks of treatment. While the primary endpoint was not reached, patients treated with Trazo/Gaba 2.5/25 mg t.i.d. showed statistically significant improvement of pain and other scores after 6 weeks and reported consistent better results in comparison to PLB on primary and secondary endpoints for the overall study duration. According to these results, the lowest dose of Trazo/Gaba FDC may be the best candidate for further clinical development to confirm the potential benefits of the FDC drug for this condition. Clinical Trial Registration NCT03749642.